CLINICAL STUDY OF TOPICAL APPLICATION OF PLATELET-RICH PLASMA IN MANAGEMENT OF CHRONIC WOUNDS AT A TERTIARY CARE CENTER - Pareek, Monika; Kumar, Ashok; JAKHAR, DIWAN; Lodha, Sanjay; Gahltot, Navratan (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: To study the efficacy and safety of platelet-rich plasma in the management of chronic wounds when applied locally. Methods: A hospital-based prospective study was conducted on 30 cases with the diagnosis of a chronic wound and fulfilling inclusion criteria by convenience sampling presented to surgical OPD and emergency in the study period of 12 months (December 2021 to November 2022) at the Dept. of Surgery, S.P. Medical College, and P.B.M. Hospital, Bikaner. Results: The mean age was 48.76±5.65 years with male preponderance, and most of the cases were rural. 36.67% of cases presented in 6–12 months; 36.67% had traumatic etiology; 30% had diabetic; 26.67% had vascular; and 6.67% had burn etiology. 53.33% of cases had a lesion on the foot, and 22% of cases had joint involvement, with a mean size of an ulcer of 8.94±2.14 cm2. 73.33% of cases had partial healing, and 26.67% had complete healing. The mean duration for complete healing was 10.5±3.4 weeks. Mean dressings were needed for the complete healing were 21.1±5.9 dressings. Conclusion: PRP was found to be useful in treating chronic ulcers. However, further controlled, randomized prospective clinical trials are necessary to definitively demonstrate its efficacy.